Zeolites in Sustainable Chemistry Synthesis, Characterization and Catalytic Applications - Xiao, Feng-Shou.; Meng, Xiangju; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book is devoted to the new development of zeolitic catalysts with an emphasis on new strategies for the preparation of zeolites, novel techniques for their characterization, and emerging applications of zeolites as catalysts for sustainable chemistry, especially in the fields of energy, biomass conversion, and environmental protection. Over the years, energy and the environment have become the most important global issues, while zeolitic catalysts play important roles in addressing them. With individual chapters written by leading experts, this book offers an essential reference work for researchers and professionals in both academia and industry. Feng-Shou Xiao is a Professor at the Department of Chemistry, Zhejiang University, China. Xiangju Meng is an Associate Professor at the Department of Chemistry, Zhejiang University, China.
Part I Novel strategies for synthesizing zeolites -- Sustainable routes for zeolite synthesis -- Ionothermal Synthesis of Molecular Sieves -- Interlayer Expansion of the Layered Zeolites -- Mesostructured zeolites -- Part II New Developments in Characterization of Zeolites -- Structure determination of zeolites by electron crystallography -- Structure Analysis in Zeolite Research: From Framework Topologies to Functional Properties -- Solid-state NMR Studies of Zeolites -- Part III Emerging Applications of Zeolites for Sustainable Chemistry -- Zeolites in Fluid Catalytic Cracking (FCC) -- Chemistry of the Methanol to Olefin Conversion -- Zeolite catalysis for biomass conversion.- Catalytic Oxidations over Titanosilicate Zeolites -- Emerging applications of environmentally friendly zeolites in the selective catalytic reduction of nitrogen oxides -- Zeolite thin films and membranes: From fundamental to applications -- Zeolites catalyzing raw material change for a sustainable chemical industry -- Part IV Conclusion -- Concluding Remarks.
Keywords: Catalysis; Renewable energy sources; Chemistry, Technical; Materials -- Analysis; Catalysis; Renewable Energy; Industrial Chemistry; Characterization and Analytical Technique